Conceptual framework of Muhamad Rashid Rida's political thought - Shuriye, Abdi Omar (Faculty of Leadership and Management-Kolej Universiti Islam Malaysia(KUIM), 2003)
Islam as an institution in which religion becomes an integral part of the system of governance and state may not sanction or recognize dichotomy between the two. Throughout the epochs of the Prophetic (622-632A.D) and the four rightly guided caliphs (632-661A.D) spiritual quality remained the determinant factor of political leadership a phenomenon that subjects the study of Islamic political science within the framer,vork of religious ideology. The demise of the Ottoman Empire however marked the beginning of a new era. in IVluslim political science, the age of colomialism, eventually leadlng to disunity and predicament and the emergence of the present political quandary of the Muslim Ummah. Thus Musnim thinkers emerged in an attempt to find solutions to the aforementioned state-of-affairs.'Few thinkers occupy prominent place in the history of conrtffmporary Islamic political science as Muhammad Rashid Rida ( I S55-l93sA.D), his views on political science are distinctive in harmonizing the liberal political ideas of his mentors namely, Afghani and Abduh, and that of his conservative students, such fls, Hassan al-Banna. Besides, Rida synthesizes reviivalist and nationalist schools in Islamfra political science. This paper aspires to evaluate the epistemological framework of Rida's views on ummatic politican science and his comtnibution to the Islamination aspect of the subject. Living in an eon where cultural-cerebral supremacy of the west became prevalent over the socio-political and economic domains of the Muslim (Jmmah, Rida forcefully opposed the material rnenaoe of the West and conjured up alternatives based upon overriding reality o{' that point irr tirne. Rida primarily spent his life as a political jor-rrnalist in an outlook of reform by introducing social and political restructure within the Muslirn political paradignr, in an attempt to bringing about transforrnatioll tl-lat would end the imbue of the Musim Ummah